A gestão escolar na educação infantil: o papel do gestor no cuidar e educar da criança - Fonseca, Valmir Cidade (Brasil, 2024)
This study aims to understand the role of the school manager in caring for and educating children in a Children's Educational Center in the city of Parintins, Am. It also proposes to identify the role of school management and its involvement in the children's teaching-learning process, verify the view of teachers and parents of students on the performance of management and describe the experiences, challenges and contributions experienced by managers within the scope of Early Childhood Education. The study takes a qualitative approach, consisting of field research, whose data collection occurred through interviews with the institution's manager and teachers, as well as the application of a questionnaire to the parents or guardians of the children enrolled. The data show that exercising the role of manager is not a simple task, as it requires facing numerous difficulties and demands required by the educational system and society in general. The excess of administrative demands has taken the manager's attention to the detriment of pedagogical issues, making her more effective participation in the education and care of children unfeasible. Therefore, the role of the manager is extremely important in the education and care of young children, because he or she has the greatest responsibility for organizing the school space, caring for affective relationships and proposing actions that enable the solution of problems that affect children's academic success and the work of teachers in early childhood education.